Immersive Low-Cost Virtual Reality Treatment for Phantom Limb Pain: Evidence from Two Cases - Ambron, Elisabetta; Miller, Alexander; Kuchenbecker, Katherine J.; Buxbaum, Laurel J.; Coslett, H. Branch (Frontiers in Neurology, 2018)
Up to 90% of amputees experience sensations in their phantom limb, often including strong, persistent phantom limb pain (PLP). Standard treatments do not provide relief for the majority of people who experience PLP, but virtual reality (VR) has shown promise. This study provides additional evidence that game-like training with low-cost immersive VR activities can reduce PLP in lower-limb amputees. The user of our system views a real-time rendering of two intact legs in a head-mounted display while playing a set of custom games. The movements of both virtual extremities are controlled by measurements from inertial sensors mounted on the intact and residual limbs. Two individuals with unilateral transtibial amputation underwent multiple sessions of the VR treatment over several weeks. Both participants experienced a significant reduction of pain immediately after each VR session, and their pre-session pain levels also decreased greatly over the course of the study. Although preliminary, these data support the idea that VR interventions like ours may be an effective low-cost treatment of PLP in lower-limb amputees.